Increase in subcutaneous adipose tissue in the frontal scalp may be associated with androgenetic alopecia and metabolic syndrome - Dayanan, R.; Bilen, A.; Ciftel, S.; Ciftel, E.; Mercantepe, F.; Demirci, T.; Bilen, H. (Verduci Publisher, 2023)
- OBJECTIVE: Recent studies have suggested that androgenetic alopecia (AGA) may be associated with other disorders, especially metabolic syndrome (MetS). This study aimed to determine whether a connection exists between MetS and AGA based on the thickness
Keywords: Metabolic syndrome; Sub-cutaneous adipose tissue in the scalp; Androgenetic alopecia